Perlindungan Hukum Terhadap Data Pribadi Masyarakat Dalam Pendaftaran Dan Verifikasi Partai Politik Sebagai Peserta Pemilihan Umum - Maad, Zulfan Husnul; handayani, widya marthauli (Wajah Hukum, 2023)
The requirements for political parties to participate in the general elections in Indonesia include passing the registration and verification stages by the General Election Commission through a platform called the Political Party Information System (Sipol). The verification process consists of administrative and factual verification, which includes research and matching of the requirements as a participant in the general election, one of which is membership in a political party. However, this membership has caused problems due to the rampant acquisition of memberships through the use of the Population Identification Number (NIK). This research aims to assert that personal data must be protected with simultaneous protection as a maximal effort to eliminate the misuse of personal data by political parties. The research method used is normative juridical by using secondary data sources and supported by primary laws, as well as a qualitative descriptive method to collect data through interviews. The results of this research show that the protection of personal data against the misuse of public names is crucial. Thus, laws that regulate the general protection of personal data can be a reference in legal protection efforts in such cases. Moreover, on October 17, 2022, the President of Indonesia has enacted Law No. 27 of 2022 concerning Personal Data Protection, which specifically (lex specialis) regulates the protection of personal data